DESIGNING AN AI-INTEGRATED CURRICULUM INNOVATION FRAMEWORK FOR HIGHER EDUCATION - Suradji, Muchamad; Khozin, Khozin; Faridi, Faridi (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: The rapid integration of Artificial Intelligence (AI) in higher education presents both opportunities and challenges for curriculum design. Purpose: This study aims to develop and validate an AI-Integrated Curriculum Innovation Framework with an Islamic Perspective, which holistically integrates technological, pedagogical, ethical, and spiritual dimensions. Method: Using an exploratory sequential mixed-methods design, qualitative data were collected through interviews and focus group discussions with 25 participants (lecturers, students, and administrators), while quantitative validation involved a survey of 115 respondents. Thematic analysis identified four core dimensions—AI Literacy, Data-Driven Personalization, Ethics & Governance, and Adaptivity & Future Skills—which were tested using Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM). Result: Results demonstrated strong construct validity, with Ethics & Governance as well as AI Literacy as a major predictor of future adaptability and skills. Integration of Islamic values ​​such as ta‘lim (education), ḥikmah (wisdom), and maqāṣid al-sharī‘ah ensuring that AI functions not merely as a technical tool, but as a catalyst for values-oriented curriculum transformation. Conclusion: Theoretically, this research bridges classical curriculum theory with AI studies; practically, the AI-Integrated Curriculum Framework has the potential to revitalize academic governance, strengthen digital literacy, and establish an adaptive, ethical, and sustainable learning ecosystem in higher education institutions.